2014
DOI: 10.14419/gjma.v2i3.2990
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Effect of Toxicant on a Three Species Food-Chain System with "Food-Limited" Growth of Prey Population

Abstract: In this paper, a mathematical model is proposed and analyzed to study the effect of toxicant in a three species food chain system with "food-limited" growth of prey population. The mathematical model is formulated using the system of non-linear ordinary differential equations. In the model, there are seven state variables, viz, prey density, intermediate predator density, density of top predator, concentration of toxicant in the environment, concentration of toxicant in the prey, concentration of toxicant in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Previously, some research work has been carried out on tri-trophic food-chain systems including toxicant effects on the survival or extinction of species using mathematical models Raveendra Babu 2014, 2016;Hallam and Luna 1984;Thomann et al 1974;Thomann and Connolly 1984). In Misra and Raveendra Babu (2014) the authors have studied the effects of toxicant in a three species food chain system with ''food-limited'' growth of prey population. In the model, the authors have assumed that the carrying capacity and growth rate of prey is affected by environmental toxicant which is being transferred to intermediate and top predator populations through food chain pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, some research work has been carried out on tri-trophic food-chain systems including toxicant effects on the survival or extinction of species using mathematical models Raveendra Babu 2014, 2016;Hallam and Luna 1984;Thomann et al 1974;Thomann and Connolly 1984). In Misra and Raveendra Babu (2014) the authors have studied the effects of toxicant in a three species food chain system with ''food-limited'' growth of prey population. In the model, the authors have assumed that the carrying capacity and growth rate of prey is affected by environmental toxicant which is being transferred to intermediate and top predator populations through food chain pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou and Shi [35] have revisited a diffusive Leslie-Gower predator-prey model and discussed the bifurcation and stability of multiple steady state solutions. In this paper Misra and Babu.A [21] have analyzed the local and global stability of the feasible equilibrium points. They have also given a comparative study with the corresponding non-toxicant system where they have observed that toxicants have very clear effects on the species if the availability of resource is limited.…”
mentioning
confidence: 99%